Pemberian Restitusi Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Seksual Berdasarkan Putusan Hakim di Pengadilan Negeri Atambua - Irene Marlen Dira Tome; Simplexius Asa; A. Resopijani (Perkara : Jurnal Ilmu Hukum dan Politik, 2023)
Along with the development of criminal acts more prevalent time occurs not only adults but also children can also be perpetrators and victims of criminal acts. This is because every child has a different condition from adults, children have physical and mental immature and are very easily influenced by other parties. Forms of legal protection from the government for children who are victims of criminal acts include compensation, compensation, and restitution. Restitution is the payment of compensation charged to the perpetrator based on a court decision with permanent legal force for material and/or immaterial losses suffered by the victim/his heirs. In this writing, the main focus will be restitution. Based on the case, the researcher formulated the main problems, namely: (1) How is the process of giving restitution to children as victims of sexual violence based on the decision of the judge in the Atambua District Court? (2) What are the supporting and inhibiting factors in the process of giving restitution to children as victims of sexual violence based on the decision of the judge in the Atambua District Court? This study uses empirical legal research methods that researchers conduct interviews with the parties concerned. Aspects of the study examined the process of restitution and the factors supporting and inhibiting the application of restitution. The results found that: (1) in terms of efforts to fulfill the right of restitution to children victims of sexual violence, law enforcement officers and victims have a role in pursuing the right of restitution. The investigator and the public prosecutor are obliged to inform the victim about the rights obtained by the victim. The victim can apply for restitution which can be done during the investigation process, prosecution, or after a decision with permanent legal force is read. (2) there are two factors that become obstacles in its implementation, namely legal factors and community factors.